PEMBUATAN STANDARISASI KERJA UNTUK MENGURANGI ANGKA PRESETTING DEVIATION PADA LINE 9 PT SKF INDONESIA - Yuselin, Nensi; Valerian, Elvin (Technologic, 2022)
PT SKF Indonesia is a global company that produces bearing s and is part of the SKF Group (SKF AB Sweden) and the Astra Group (Astra Otoparts). PT SKF Indonesia always improves the quality of the changeover so that it can produce bearing quality that meets company standards. In the changeover process, the type of deviation with the highest number is flow process deviation on line 9. After making observations, it was found that the problem was in the flow process process. This causes the flow process deviation to be high. The problem is that there is no work standard in the process flow process. Therefore, the authors conducted further research using the DMAIC method to find the root of the problem. After finding the root of the problem, the authors made improvements, namely standardizing the work flow process by making presetting flow processes, return tooling flow processes, presetting room layouts, catalogs, SOP tooling preparation, SOPs for returning to cabinets, SOP tooling cleaning, critical tooling parameters and making controls, standardization for monitoring, standardization by making, standardization control boards, monitoring checklists. After repairs and evaluations were carried out, the presetting rate decreased by 71.5% from 14 deviations in 3 months to 4 deviations in 3 months.